Writing in the disciplines - Deane, Mary; O'Neill, Peter (Universities into the 21st century, 2011)
"Writing in the Disciplines is an expanding field in which subject specialists and writing specialists collaborate to provide academic writing tuition to student writers. This book places WiD in its theoretical and cultural contexts and reports on initiatives taking place at a range of UK Higher Education Institutions"--